Regulasi dan Kontrol Diri Pada Perilaku Konsumtif Santri Di Era Less Cash Society - Susilawati, Ririn; Maryati, Wiwik; Faqih, Abdulah (Al Iqtishod: Jurnal Pemikiran dan Penelitian Ekonomi Islam, 2024)
At this time santri have become part of a non-cash society, or less cash society, one of which is the Sidogiri Pasuruan Islamic Boarding School students in East Java, who use electronic money with the Basmalah E-maal brand. In carrying out transactions every day in the Islamic boarding school environment, electronic money is not only used for administrative payments. Santri can also shop, and guardians of students can send money allotments via transfer to electronic money. With the convenience of this technology, it is necessary to have regulation and self-control so that students can control their consumption behavior in accordance with consumption limits in Islam. The purpose of this study was to determine regulation and self-control in the consumptive behavior of students in the less cash society era. This research uses a qualitative-descriptive approach. The data collection techniques used are observation, in-depth interviews, and documentation. The source triangulation in this study was the Basmalah Shop admin and the student guardians who became informants. The results of this study indicate that the self-regulation of students is supported by the Sidogiri Islamic Boarding School environment, which has a maximum spending limit policy and a mandatory savings program. Meanwhile, students' self-control can be assisted by budget constraints to reduce their expenses.